Design thinking implementation for innovation: An organization's journey to ambidexterity. Issue 6 (18th October 2021) - Randhawa, Krithika; Nikolova, Natalia; Ahuja, Sumati; Schweitzer, Jochen
Abstract: Implementing design thinking for innovation (DTI) is seen as a way to balance exploration and exploitation, and thus attain an ambidextrous innovation portfolio. Yet, transitioning to ambidexterity is challenging, and is often met with inertia. So how can managers implement DTI as a path toward ambidextrous innovation? In this article, based on an in‐depth longitudinal case study of a leading Australian property development firm and drawing on rich primary and secondary data collected over four years, we examine how middle managers leveraged DTI to respond to inertia generatively, and how this process helped shift the cognitive frame of the organization toward ambidexterity. In our case, the middle manager implemented three DTI practices—(1) creative problem‐solving, (2) sprint execution, and (3) creative confidence— to transition the organization's cognitive frame from an explorative to exploitative, to ultimately an ambidextrous innovation frame. Our argument is that these DTI practices trigger three generative mechanisms—frame flexibility, co‐optation, and collective sensemaking—to support this transition. Drawing on these insights, we develop a process framework of how different DT practices and related generative mechanisms can be deployed flexibly to adapt to the interim (explorative and exploitative) innovation objectives over time. We argue that freezing the innovation frame in each phase can trigger a generative response to inertia, which enables the organization to transition more radically to an ambidextrous innovation portfolio. We thus contribute to the limited design thinking research on the role of cognition in DTI implementation, and more generally to innovation management and ambidexterity research on how leveraging DTI to achieve an ambidextrous innovation portfolio is an emergent and adaptive process.